2017
DOI: 10.1073/pnas.1713292114
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-dependent mechanism for controlling triglyceride secretion from the liver

Abstract: SignificanceThe liver secretes lipids in a controlled manner despite vast changes in its internal lipid content. This buffering function of the liver is essential for lipid/energy homeostasis, but its molecular and cellular mechanism is unknown. We show that motor protein kinesin transports lipid droplets (LDs) to the endoplasmic reticulum (ER) in liver cells, engineering ER−droplet contacts and supplying lipids to the ER for secretion as lipoprotein. However, when fasting induces massive lipid accumulation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
95
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(104 citation statements)
references
References 42 publications
4
95
0
Order By: Relevance
“…Recent evidence suggests that, during the fed state, cLDs are transported toward the plus end of microtubules by kinesin-1 near the smooth ER in liver cells (29). Rai et al observed that most cLDs in rat hepatoma McA-RH7777 cells were found at the extreme periphery where the microtubule plus end exists (29). Similar observations were made with human HHL-17 hepatocytes and liver sections from fed rats.…”
Section: Synthesis and Mobilization Of Lipids For Lipoprotein Assemblymentioning
(Expert classified)
See 2 more Smart Citations
“…Recent evidence suggests that, during the fed state, cLDs are transported toward the plus end of microtubules by kinesin-1 near the smooth ER in liver cells (29). Rai et al observed that most cLDs in rat hepatoma McA-RH7777 cells were found at the extreme periphery where the microtubule plus end exists (29). Similar observations were made with human HHL-17 hepatocytes and liver sections from fed rats.…”
Section: Synthesis and Mobilization Of Lipids For Lipoprotein Assemblymentioning
(Expert classified)
“…It is also known that cLDs interact with the ER, and thus fatty acids derived from the hydrolysis of triacylglycerols that reside in cLDs tethered to the ER can be preferentially delivered to the ER and utilized for lipid re-synthesis and lipoprotein assembly. Recent evidence suggests that, during the fed state, cLDs are transported toward the plus end of microtubules by kinesin-1 near the smooth ER in liver cells (29). Rai et al observed that most cLDs in rat hepatoma McA-RH7777 cells were found at the extreme periphery where the microtubule plus end exists (29).…”
Section: Synthesis and Mobilization Of Lipids For Lipoprotein Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…Cytosolic lipid droplets (LDs) store triglycerides (TGs) that are substrates for energy and membrane synthesis in most tissues (Murphy, 2012; Thiam and Beller, 2017). LDs are catabolized to supply fatty acid for assembling VLDL (very low density lipoprotein) particles in the smooth ER (sER) of hepatocytes (Gibbons et al, 2004; Lehner et al, 2012; Rai et al, 2017). VLDL is secreted from the liver into blood, where it is detected as serum TG.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations have demonstrated that both functions regulate normal hepatic physiology and when impaired contribute to the pathophysiology of liver disease. (1) The full spectrum of autophagy's metabolic functions in the liver has recently begun to be defined. The realization that insulin increases and glucagon decreases cellular levels of both autophagy and lipid breakdown led to the discovery that autophagy regulates hepatocyte lipid content and the development of hepatic steatosis.…”
Section: A Novel Mechanism Of Starvation-stimulated Hepatic Autophagymentioning
confidence: 99%